Quality of life and sexual function after TVT surgery versus Bulkamid injection for primary stress urinary incontinence: 1 year results from a randomized clinical trial - Itkonen Freitas, Anna-Maija (Int Urogynecol J, 2020)
INTRODUCTION AND HYPOTHESIS: To assess changes in quality of life (QoL) and sexual function outcomes at 1 year after tension-free vaginal tape (TVT) versus polyacrylamide hydrogel injection (PAHG). METHODS: In a randomized trial comparing TVT (n = 111) and PAHG (n = 113) treatments of stress urinary incontinence (SUI), we compared urinary incontinence and health-related QoL using the Urogenital Distress Inventory (UDI-6), Incontinence Impact Questionnaire, Short Form (IIQ-7), Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) and RAND-36 Item Health Survey (RAND-36) at baseline and 1 year. RESULTS: UDI-6 and IIQ-7 showed improved incontinence-related QoL (p = 0.001) from baseline in both groups except for difficulty emptying the bladder and pain/discomfort. At 1 year, TVT patients experienced less urinary symptom-related distress compared to PAHG (p < 0.001). Sexual function improved in both groups (p < 0.001 for TVT and p = 0.01 for PAHG) with higher scores for the physical section subscale (p < 0.001) for TVT. Health-related QoL (RAND-36) improved from baseline in both groups in physical and social functioning (p < 0.001) with better outcome in the TVT group for physical functioning (p < 0.001). Increase in pain from baseline (p = 0.02) was detected for TVT, but not for PAHG. However, there was no difference between the groups (p = 0.78). CONCLUSIONS: In primary SUI, TVT and PAHG treatments both improved QoL and sexual function at 1 year. However, incontinence and health-related QoL scores were better in the TVT group. More pain compared to the baseline was reported after TVT, although there was no difference between groups. Clinical significance needs to be evaluated in long-term follow-up.